2021
DOI: 10.1109/lra.2021.3088779
|View full text |Cite
|
Sign up to set email alerts
|

Improving Visual Place Recognition Performance by Maximising Complementarity

Abstract: Visual place recognition (VPR) is the problem of recognising a previously visited location using visual information. Many attempts to improve the performance of VPR methods have been made in the literature. One approach that has received attention recently is the multi-process fusion where different VPR methods run in parallel and their outputs are combined in an effort to achieve better performance. The multi-process fusion, however, does not have a well-defined criterion for selecting and combining different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 48 publications
(82 reference statements)
0
15
0
Order By: Relevance
“…[11] presents a three-tier hierarchical multi-process fusion system which is customizable and may be extended to any arbitrary number of tiers. Another interesting idea that explores the notion of complementarity between multiple VPR techniques is introduced by [12]. A McNemar's test like approach is used to test out the level of complementarity between different VPR techniques.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…[11] presents a three-tier hierarchical multi-process fusion system which is customizable and may be extended to any arbitrary number of tiers. Another interesting idea that explores the notion of complementarity between multiple VPR techniques is introduced by [12]. A McNemar's test like approach is used to test out the level of complementarity between different VPR techniques.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rather than another attempt to develop a new VPR technique from scratch, a well received and an intuitive solution has been put forward in [10], [11] that introduces the concept of multi-process fusion between different VPR techniques. Furthermore, to refine the idea of multi-process fusion, [12] proposes a framework evaluating the complementarity of different VPR techniques with each other. This is based on a functional piece of knowledge collected through empirical data that different techniques have the potential of complementing each other's weaknesses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, evidence has been accumulating that certain combinations of modalities are more effective than others on specific datasets [6], [12]. However, both these works rely on either a training set, or access to the full ground-truth information for a given dataset.…”
Section: A Fusing Multiple Modalities For Improved Vprmentioning
confidence: 99%
“…By using multiple VPR techniques simultaneously, limitations with one technique (in a specific environment) can be offset with the inclusion of additional techniques that may not have such limitations. More recent work has shown that certain combinations of techniques are more effective than others on specific datasetsa phenomenon that has been termed the complementarity of different combinations of techniques [6], [12].…”
Section: Introductionmentioning
confidence: 99%